Facile synthesis of cobalt and nitrogen co-doped graphene networks from polyaniline for oxygen reduction reaction in acidic solutions. Issue 10 (19th February 2016) - Peng, Shuqin; Jiang, Hongmei; Zhang, Youming; Yang, Lu; Wang, Shuqin; Deng, Wenfang; Tan, Yueming
Abstract : Co and N co-doped graphene networks derived from polyaniline nanofibers can show high oxygen reduction activity in acidic solutions. Abstract : Direct pyrEmail:o lysis of a mixture comprising polyaniline nanofibers and cobalt(ii ) nitrate is found to be a simple and scalable approach to the synthesis of Co and N co-doped graphene networks for oxygen reduction reaction in acidic solutions with high catalytic activity and excellent durability.